Empresas recuperadas por trabalhadores: limites à consolidação das ERTS na experiência brasileira e argentina - Bezerra, Maria Taynara Ferreira (2021)
This dissertation aims to comparatively analyze the experiences of companies recovered by workers (ERTs) from Argentine and Brazil, in order to identify the limits to the consolidation of these initiatives as an alternative to closing companies, considering that it is a social, legal, political and economic phenomenon, which occurs in times of crisis, and is based on the subversion of the right to private property and self-management as a model of organization and work. The crisis of neoliberalism in the 1990s, crossed by economic dependence, deindustrialization, productive restructuring and financialization of the economy in Latin America, led to bankruptcy and indebtedness of many entrepreneurs in the region, causing the abandonment and closure of numerous companies. Dissatisfied by the loss of their jobs and the unfeasibility of material conditions for survival, workers promoted occupation strikes and, through these, began a process of productive recovery of these enterprises, characterizing the phenomenon called Companies Recovered by Workers. It was used the dialectical historical materialist method, given that the analysis started from the material reality of the ERTs, considering their contradictions and limits within the historical process and the social totality in which they are inserted, understanding that it is not a phenomenon isolated with an end in itself, but an answer to the political and economic transformations experienced by society. With regard to the procedural methodology, bibliographical and documentary research was used. It was concluded that, in addition to appearing as an alternative to bankruptcies and crisis processes, even as a consequence of the process, ERTs point to another possible mode of sociability. For this reason, they are limited by the legislative and legal structures, which serve to maintain the current production system. Despite this, one cannot give up the use of available legal tools, such as the cooperative form, which even in a limited way, serve to legalize these self-managed ventures. Recovered companies also face limits from the point of view of self-management, as these initiatives sometimes reproduce, within them, hierarchical structures of conventional firms, as well as the problem of access to credit and institutional and popular support